Pengaruh Kualitas Produk, Harga, Citra Merek dan Iklan Terhadap Keputusan Pembelian Yamaha Motor Matic di Purwodadi (Study Kasus Pada Konsumen Pengguna Yamaha Motor Matic di Purwodadi) - Ma'ruf, Hasan, Drs. Wiyadi, S.E., Ph.D (2015)
This study aims to analyze the effect of product quality, price, brand image and advertising on purchasing decisions, The sample in this study is that people who use the product Purwodadi Yamaha Motor Matic 100 respondents, With convenience sampling technique sampling, Data analysis method used is multiple regression and hypothesis testing. Based on the results of the quality of the product (X1) has a significant influence on purchase decisions (Y). Variable price (X2) have a significant influence on purchase decisions (Y). Brand image variable (X3) have significant influence on purchase decisions (Y). Variable advertisements (X4) has a significant influence on purchasing decisions, while simultaneously the variable quality of the product (X1), price (X2), brand image (X3) and advertising (X4) on purchase decisions (Y), so that the model use is appropriate and determination coefficient analysis results of research known right (fit) and a variation of the variable changes in the purchasing decision can be explained by the variable quality of the product (X1), price (X2), brand image (X3) and advertising (X4) by 52.6% because the value of R square (R2) obtained at 0.526. While the rest of 47.4% is explained by other variables outside the model